APLIKASI PERHITUNGAN BIAYA POKOK PENYEDIAAN TENAGA LISTRIK DI SUMATERA UTARA SUB SISTEM TRANSMISI - ERBIN SITORUS (LP2MTBM MAKARIOZ, 2019)
The issue of the availability of electricity has become the main issue in the community along with the increasing socio-economic growth of the community itself. Electricity that is reliable and economical is expected to drive economic growth, so that electricity availability is needed that is sufficient to meet the needs of the community. Increasing the procurement of electricity requires a large investment to meet the operating and maintenance costs of the electric power system, so it is necessary to make a description of the cost of production. Thus it is necessary to make a financial description to determine the economic value of electricity so that we can determine the price of electricity that is appropriate and create a reliable system reliability. And to make it easier, it is necessary to make a software based on visual studio programming language. The aim is to produce a software to calculate the basic cost of supplying electricity for the transmission sub-system as well as obtaining the basic cost of supplying electricity especially for North Sumatra for a period of 10 years, from 2011 - 2020. The results showed that the basic cost of providing electricity for the transmission sub-system changes every year where the highest is in 2014 which is Rp 174,696.- per kWh and the lowest in 2020 is Rp 109.95.- per kWh.